(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines how Rosalkogoltabakkontrol’s information interaction with executive authorities and the use of digital systems increase the effectiveness of state control over the circulation of excise goods and excise revenues, as well as the necessity of further digital integration and the implementation of predictive analysis.